Love and the Sharing of Ends - Westlund, Andrea C. (My University, 2005)
This working paper examines love and union through philosophical writings. It is argued that lovers create a new perspective, and share the ends of that perspective rather then take on each other's individual ends.
Keywords: Philosophy; Love; Union